Vocal variations in speech following cognitive cueing - Tiffy George Roy; Yeshoda K (Journal of All India Institute of Speech and Hearing, 2011)
Voice plays an important role in signaling speaker affect. Literature has stated many ways to elicit emotional voice sample. All of the methods that have been used have both advantages and disadvantages. The use of cognitive cues as a task elicitation method stems from cognitive-behavioral therapy and focuses on prompting the individual to think and feel about a task prior to its completion. The present study attempted to understand the usefulness of cognitive cueing in eliciting vocal changes in speech, in terms of variations in mean speaking fundamental frequency (MSF0) and related parameters and sentence duration when different emotions were employed. Sentences were constructed for five emotions: neutral, happy, anger, fear and sad and the same were graphically represented on Acards. Cognitive cues were also constructed for each of these sentences. Twenty (equal numbers of females and males) under graduate students of a college, aged between 20 to 25 years who were competent in English language use were the participants of the study. Each participant was asked to read the sentences of different emotions thrice. First trial, uncued condition: without the cognitive cues, cued condition: second and third trials, after the presentations of cognitive cues. Real Time Pitch of CSL 4500 was used for analyzing the read samples. The results in general, revealed changes in means values for the MSF0 and its related parameters and sentence duration in cued conditions compared to uncued conditions for all emotions. Therefore, it could be concluded that cognitive cueing brought about quantifiable changes in vocal attributes. Further, the results of the study strengthen the view that use of cognitive cues stimulates voice patterns that would alter speaking styles of individual. This would have practical implications in management of individuals with communication disorders and professional voice users.